The Correlation Between Idiopathic Pulmonary Fibrosis and Lung Cancer - Liu , Yuming (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The prevalent chronic lung condition known as idiopathic pulmonary fibrosis (IPF) is defined with the repeated scarring of pulmonary tissues. About 3 million individuals are impacted globally, and that figure is only increasing. There are no effective treatments available right now to help IPF sufferers with their symptoms. The lungs, one of the essential organs in charge of exchanging oxygen, are affected by lung cancer, a terrible condition that can be fatal. It affects both men and women of all ages and is the main reason for cancer-related deaths globally. This research focuses on the correlation between similar risk factors and related causes of these two diseases. By discussing the transforming growth factor β (TGF-β) and telomeres, it would be able to see how the two diseases are related. In addition, targets for the vaccination will also be analyzed, and the current stages of clinical therapeutic methods will be discussed.